Forgiveness Dan Fatherless Pada Remaja Korban Toxic Relationship - Zuroida, Aironi; Agustin, Ardianti (Universitas Darul Ulum, 2025)
Adolescence is an emotionally challenging period, with adolescents often facing unstable feelings and erratic behavior patterns. The adolescent phase is characterized by intense peer and romantic relationships, which are often the main focus of their lives, usually leading to toxic relationships. The phenomenon of Fatherlessness, the absence of a father figure, can exacerbate the emotional impact, especially on girls, who tend to have difficulties in building healthy relationships. This study shows that Forgiveness plays an important role in helping adolescent victims of toxic relationships reduce the negative impact of Fatherlessness. The Forgiveness process allows individuals to let go of feelings of resentment and build better self-control. The method used in this study is a quantitative approach with a purposive sampling technique and data collection through Forgiveness and Fatherless scale questionnaires. The results showed a significant relationship between the level of Forgiveness and Fatherlessness, which has implications for improving adolescents' emotional well-being and their ability to move out of harmful relationships.